2021
DOI: 10.1093/jimb/kuab005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of action of ribosomally synthesized and posttranslationally modified peptides (RiPPs)

Abstract: Natural products remain a critical source of medicines and drug leads. One of the most rapidly growing superclasses of natural products is RiPPs: ribosomally synthesized and posttranslationally modified peptides. RiPPs have rich and diverse bioactivities. This review highlights examples of the molecular mechanisms of action that underly those bioactivities. Particular emphasis is placed on RiPP/target interactions for which there is structural information. This detailed mechanism of action work is critical tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 252 publications
1
76
0
Order By: Relevance
“…We adopted Boltzmann averaging due to its relevance to characterize energy state of canonical ensemble in thermodynamic equilibrium. 83,84 The computed energy gap of 2.7 kcal/mol is consistent with the experimental trend for ∆H (i.e., 4 kcal/mol). The agreement is particularly good considering that we neglected vibrational zero-point energy corrections due to the high cost of computing Hessians for such large systems.…”
Section: Results and Discussion 3a Loss Of Hydrogen Bonding Interactions Elevates The Energy State Of Conformersupporting
confidence: 78%
“…We adopted Boltzmann averaging due to its relevance to characterize energy state of canonical ensemble in thermodynamic equilibrium. 83,84 The computed energy gap of 2.7 kcal/mol is consistent with the experimental trend for ∆H (i.e., 4 kcal/mol). The agreement is particularly good considering that we neglected vibrational zero-point energy corrections due to the high cost of computing Hessians for such large systems.…”
Section: Results and Discussion 3a Loss Of Hydrogen Bonding Interactions Elevates The Energy State Of Conformersupporting
confidence: 78%
“…Thiazolines and thiazole are replete in natural products 4244 and synthetic drug-like small molecules, 8,9 and calculations confirm the expected decrease in conformational freedom that derives from aromatic and/or sp 2 character within the peptide backbone. 45 This finding and the leader-independent nature of MicD-F and ArtGox-mediated thiazol(in)e biosynthesis inspired us to explore substrates in which the site of cyclodehydration/dehydrogenation is embedded within a stable protein fold ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 87%
“…Therefore, the first two residues IL1 and Dhb2 associated with N-ter lanthhionine ring A and methyl lanthionine ringB forms a pocket that encloses the lipidII. This interaction is ensured by the hydrogen binding between the pyrophosphate group of lipidII and the backbone amides [26] (Figure 5). Wiedemann et al have demonstrated that C-terminal region is crucial for binding to membrane with a negative surface charge.…”
Section: Structural Analysis: Amino Acids and Activitymentioning
confidence: 99%
“…The study of bacteriocin structures and amino acids composition helps to understand their detailed mechanism of action. This feature is critical towards the development of bacteriocins as therapeutics and can also be used to prioritize hits in their genome mining studies [26]. Hence a library of synthetic bacteriocin variants served as a tool; to recognize key residues responsible for activity and could continue to inspire the development of new therapeutic agents [27].…”
Section: Introductionmentioning
confidence: 99%